Psychological Safety of Educational Environment as a Condition of Positive Development of Emotional and Personal Side of Adolescents - Bukareva A. R. (Psychologically Safe Educational Environment: Design Problems and Development Prospects, 2020)
the following article substantiates the importance of psychological safety within educational environment. One of the characteristics of adolescence is a development of emotional and personal side of a child. In this period the basics of conscientious behavior and moral settings are formed. Theoretical research and practical workings, which are devoted to this problem, point on the fact that one of the main conditions of adequate development of this side is a formation of psychologically safe environment, primarily in the educational organization.
Keywords: подростки; образовательная среда; психологическая безопасность; educational environment; psychological safety; teenagers; эмоционально-личностная сфера; emotional and personal side